NOTA SOBRE SUERIA RECTINERVIS MENENDEZ DEL CRETACICO INFERIOR DE LA FORMACION BAQUERO, PROVINCIA DE SANTA CRUZ (Ameghiniana, 2013)
The present note is an emendation of the original diagnosis of the Baqueró Formation (Santa Cruz Province). Some cuticle fragments have been studied with the Scanning electron microscope.